Morphological and molecular characterization of a brand-new isolate of entomopathogenic nematode, Steinernema feltiae (Filipjev) (Rhabditida: Steinernematidae) from the Uzbekistan (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Steinernema feltiae isolate Sf:1 changed into recovered from one soil pattern gathered from the Surkhandarya region, Uzbekistan. The new isolate may be prominent from different isolates through morphologic and morphometric data, and rRNA sequences. The first generation male is characterized through spicule duration 79,5 (73±87) mm, SW ratio [(spicule length/anal body diameter)*100] 160 13 (137±177), GS ratio GS [(gubernaculum/ spicule length)*100] 79 8 (62±87), genital papillae association and the second one technology male through a mucron 10 1 (9±11) mm long. For the infective juvenile, the frame is 883 82 (754±975) mm long, lateral fields with 8 similarly evolved ridges, head smooth, barely offset, massive gonad primordium cells, a protracted hyaline tail portion (identical to 1/2 of of tail duration), and pore-like phasmid at 41% of the tail duration to the semicircle anus are the differentiation factors